Evaluation Of The Recreational Potential Of Kutahya Urban Forest - Cetin, Mehmet; Sevik, Hakan; Canturk, Ugur; Cakir, Cansel (Aperta, 2018)
Kutahya urban forest has an important historical value and great potential because of its outstanding natural and cultural heritage. It is an area that can make an important contribution to the entire region. But in order to do so, making long-termplans for the area and its surroundings, creating the necessary infrastructure, and promoting it locally and internationally are required. This study deals with the recreational tourism resources of Kutahya urban forest that include its historical, cultural, and natural landscape to determine its potential classification in terms of values that can be a source of tourism activity and are intended to be mapped. For this purpose, the value of the tourism resources that constitute Kutahya urban forest's values such as maps, photos, and surveys were evaluated in light of data collected as a result of work done in the area and of existing and potential recreational activities. Then the appropriate fields for the specified activities creating a digital base were determined. During the evaluation and processing of data, they were used to map the ArcGIS program. In conclusion, Kutahya urban forest's recreational resources including its historical, cultural, and ecological values were identified and mapped.